2022
DOI: 10.3389/fpsyg.2022.801283
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor Bottom-Line Mentality, Performance Pressure, and Workplace Cheating: Moderating Role of Negative Reciprocity

Abstract: Employee cheating at the workplace has reached epidemic proportions and is putting a significant dent on the revenues of corporations. This study evaluates workplace cheating behavior as a consequence of supervisor bottom-line mentality with performance pressure as the mediating mechanism. Most importantly, it scrutinizes the moderating function of negative reciprocity belief in the relation between bottom-line mentality, performance pressure, and cheating in a moderated-mediation model, through the lens of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 110 publications
0
27
0
Order By: Relevance
“…As for public sector employees, one of the most important factors is performance pressure. It is influenced by bottom-line mentality, which leads to workplace cheating behavior ( Kamran et al, 2022 ). The strength of performance pressure depends on the coping process; during this process, individuals may categorize two types of stressors: challenge and hindrance stressors.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…As for public sector employees, one of the most important factors is performance pressure. It is influenced by bottom-line mentality, which leads to workplace cheating behavior ( Kamran et al, 2022 ). The strength of performance pressure depends on the coping process; during this process, individuals may categorize two types of stressors: challenge and hindrance stressors.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Firstly, leaders with a bottom-line mentality set high performance goals for employees in order to ensure the financial performance of the organization, making it difficult for employees to balance safety and task performance. Excessive work stress and anger at leaders for belittling safety make employees vulnerable to falling into a state of emotional exhaustion [ 52 , 53 ]. Secondly, in order to better achieve their bottom-line goals, leaders may force employees to work for longer and more intensely, making it difficult for employees to recover their emotional resources [ 29 , 54 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The effect of generalized reciprocity (relative to negative reciprocity) on employees' compliance behavior Based on SET, a generic model of social exchange proposes two paths of exchange: if an organization provides benefits to employees, employees tend to engage in positive behaviors or outcomes for the organization; and if an organization harms employees, they may show negative behaviors or results for the organization (Cropanzano et al, 2017). Previous literature suggests that GR and NR differently influence employees' behaviors (Restubog et al, 2010;Kamran et al, 2022). However, the potential of GR relative to other forms of exchange (e.g., NR) to build strong social relations is the subject of debate in SET (Whitham, 2021).…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…GR and NR are intrinsic because they reflect organizations’ altruism and self-interest, respectively ( Sahlins, 1972 ). Previous studies showed that they could differently influence employees’ psychological states and behaviors, such as autonomous or intrinsic motivation ( Liu et al, 2021 ), deviant ( Restubog et al, 2010 ), or cheating behavior ( Kamran et al, 2022 ), affective commitment ( Quratulain et al, 2018 ), and social entrepreneurship intention ( Xiang and Zhang, 2022 ). Previous studies have demonstrated a generic model of SET social exchange ( Cropanzano et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%